2004
DOI: 10.1002/cphc.200300972
|View full text |Cite
|
Sign up to set email alerts
|

Cuii in Liquid Ammonia: An Approach by Hybrid Quantum‐Mechanical/Molecular‐Mechanical Molecular Dynamics Simulation

Abstract: To investigate the solvation structure of the Cu(II) ion in liquid ammonia, ab initio quantum-mechanical/molecular-mechanical (QM/MM) molecular dynamics (MD) simulations were carried out at Hartree Fock (HF) and hybrid density functional theory (B3 LYP) levels. A sixfold-coordinated species was found to be predominant in the HF case whereas five- and sixfold-coordinated complexes were obtained in a ratio 2:1 from the B3 LYP simulation. In contrast to hydrated Cu(II), which exhibits a typical Jahn-Teller distor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…The main advantage of this extension is the possible renunciation of non-Coulombic interaction potentials between core zone particles and particles located in the MM region. The versatility of this framework has been proven in the past for cations, anions, , as well as small organic molecules. , The simulations of the two isomers were carried out in cubic boxes with a side length of 39.2 Å, each containing 2000 water molecules. As Cu(II) was placed in the center of the core region, its radius was chosen to be 1.0 Å.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The main advantage of this extension is the possible renunciation of non-Coulombic interaction potentials between core zone particles and particles located in the MM region. The versatility of this framework has been proven in the past for cations, anions, , as well as small organic molecules. , The simulations of the two isomers were carried out in cubic boxes with a side length of 39.2 Å, each containing 2000 water molecules. As Cu(II) was placed in the center of the core region, its radius was chosen to be 1.0 Å.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The mean bonding energy evidently increases from the 59.9 kcal/mol for [Cu­(H 2 O) 6 ] 2+ to the 92.6 kcal/mol for [Cu­(NH 3 ) 4 ] 2+ . Thus, the stability increase of copper­(II) species in ammoniacal solutions could result in the decrease of their reactivity. , …”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that the water exchange at several metal ions including calcium(II) significantly increases upon complexation by heteroatoms such as nitrogen. [75][76][77][78] Also in our case EDTA is coordinating with two nitrogen atoms towards the calcium(II) ion and the mean residence time for water drops approx. an order magnitude from 40-60 ps to 2.75 ps, thus being in accordance with the literature.…”
Section: Dynamics Of [Caedta] 2− and [Mgedta] 2−mentioning
confidence: 91%